DETERMINAN PEMILIHAN KARIR AKUNTAN - muzayyanah muzayyanah (Pusat P2M Politeknik Negeri Batam, 2021)
The goal of this research is to find out what factors influence accounting students' decision to pursue a career as an accountant (public accountants, corporate accountants, teaching accountants, government accountants). The variables of consideration of the job market, work environment, financial rewards/salaries, and professional training are used to measure the factors that influence career choice. The respondents for this study were 72 accounting students from Muhammadiyah University of Cirebon's regular class who were in their 5th and 7th semesters. Multiple regression analysis with SPSS version 22 was used as the analytical method in this study. The findings revealed that labor market considerations, financial/salary rewards, and professional training had no significant impact on accounting students' decision to become accountants, whereas the work environment had a significant impact. accounting in order to pursue a career as an accountant.